Decreased dengue cases attributable to the effect of COVID-19 in Guangzhou in 2020. - Liyun Jiang; Yuan Liu; Wenzhe Su; Wenhui Liu; Zhicong Yang (PLoS Neglected Tropical Diseases)
The dengue fever epidemic in Guangzhou may have been affected by the Coronavirus Disease 2019 (COVID-19) pandemic. The number of dengue cases dropped drastically in 2020, and there have been only 2 local cases, suggesting that dengue has not become endemic in Guangzhou.